Mobility, migration, and rural-urban changes - Garrett, James L. (International Food Policy Research Institute, 2005)
Each year millions of people in low-income countries uproot themselves from rural homes to take their chances in a new setting. But who are these migrants? Where do they go and why? What becomes of individuals and families when they move? Recent studies in Bangladesh, the Philippines, and Vietnam provide insights into the reasons for migration and how migration can play a part in a household’s strategy to escape poverty. They indicate an urgent need for policymakers to understand that migration and mobility need not be threats. On the contrary, migration can offer opportunities for economic growth and livelihood security.